Featuring the application of biochemistry in dental practice through a self-directed assignment: A descriptive study - Nazlee Sharmin; Ava K. Chow (PLoS ONE, 2026)
Background With advancements in the fields of treatment, diagnosis, and genomics, knowledge of cellular biochemistry is becoming increasingly crucial for oral health professionals. However, dental students often feel demotivated to study foundational-level biochemistry because they are overwhelmed by the volume and complexity of the material and fail to recognize its relevance to dental practice. To address this, we developed a focused, self-directed assignment for 1 st -year Dental Hygiene (DH) students to enhance their understanding of protein structure and underscore the application of this knowledge in dental practice. Methods The assignment was developed in quiz-style using Google Forms and integrated into a foundational-level biochemistry course as a supplementary activity. The activity included follow-up questions asking students about their perceived accomplishments and confidence in understanding protein structure and function. A descriptive study was conducted to explore students’ perceptions of the assignment and its impact on their understanding of protein structure and function. Students’ anonymous responses to the follow-up questions and their performance on the assignment were analyzed for the study. Descriptive statistics were calculated from the data using Microsoft Excel. Results Although the assignment was not mandatory, 86% of the class (n = 25) completed it, achieving an average score of 6.04 out of 10. Sixty percent of participants (n = 15) reported improved knowledge of protein structure-function relationships, and 48% (n = 12) indicated that completing the assignment helped them understand how a simple change in protein sequence can lead to significant changes in protein structure and function. Conclusion While the assignment included a limited number of follow-up questions, which restricted our ability to explore student perceptions in detail, it demonstrates the potential of a well-designed, interactive, case-based assignment to stimulate student motivation by highlighting the relevance and application of biochemistry content in the future dental profession.